Evaluation of Antibiotic Resistance in Escherichia Coli within Nosocomial Urinary Tract Infections in Primary and Hospital Care Facilities - Atheer Riyadh Jassim; Amar Mahmood Abdalrazak; Yaseen Saad Sulaiman (Academic Journal of Clinicians, 2025)
Background: Morbidity from urinary tract infections is high; of all reported infections worldwide, more than 30% are due to UTIs, of which the most common uropathogen is Escherichia coli (E. coli). Empirical prescription of antimicrobials for UTIs is common practice; consequently, bacterial resistance to antimicrobials has increased globally, with a consequent decrease in the effectiveness of empirical treatment. Objective: To determine the in vitro resistance of the most frequent uropathogen, Escherichia coli, to various antimicrobials in our Health Sector and to deduce empirical treatment options. Material and methods: Retrospective descriptive epidemiological study carried from January 1, 2022 to December 31, 2024, E. coli strains isolated from urine cultures of patients from Primary and Hospital Care in the our health Sector were studied. A total of 42004 samples were processed. The sensitivity to eleven frequently used antibiotics was determined. The existence of statistically significant differences in sensitivity in the years studied was analyzed, comparing their corresponding 95% confidence intervals (Fisher’s method). Results: E. coli was the most frequently isolated bacterium during the study period. The resistance has been maintained below 4% against fosfomycin and nitrofurantoin and below 12% against third-generation cephalosporins. In cefuroxime and amoxicillin-clavulanic a significant increase in resistance has been observed in hospital strains with respect to those of the community in this period. The highest levels of resistance (greater than 20%) were found in the antibiotics administered orally and frequently indicated in uncomplicated urinary infections: trimethoprim-sulfamethoxazole, ciprofloxacin and amoxicillin. Conclusion: Fosfomycin, nitrofurantoin or second-generation cephalosporins was the first choice treatment for UTIs Cite the article as: Jassim A.R., Abdalrazak A.M., Sulaiman Y.S., Evaluation of Antibiotic Resistance in Escherichia Coli within Nosocomial Urinary Tract Infections in Primary and Hospital Care Facilities. Academic Journal of Clinicians, 2025; 7 (3): 105-13.